A COMPARATIVE STUDY OF DISCOURSE MARKERS IN ENGLISH AND UZBEK YOUTH DIGITAL INTERACTION: https://doi.org/10.5281/zenodo.17283028 - Hamdamov , Foziljon; Rabbiyeva , Ozoda (International scientific and practical conference, 2025)
This paper compares the use of discourse markers in English and Uzbek youth digital communication. The data consist of 200 chat excerpts (100 in English and 100 in Uzbek) collected from popular social media and messaging platforms. Both quantitative and qualitative methods were applied to examine their frequency and functions. The results show that while discourse markers in both languages serve similar purposes—structuring discourse, expressing stance, and maintaining solidarity—their forms differ. English youth most often use like, you know, and well, whereas Uzbek youth rely on ha, endi, and bilasanmi. The study also reveals cross-linguistic influence, as English markers such as ok and like appear frequently in Uzbek chats. The findings highlight that discourse markers are universal tools of interaction, yet also culture-specific, reflecting both global and local features of youth digital communication.